Modelling Domestic Tourism Demand in Australia A Dynamic Panel Data Approach - Yap, Ghialy (Economic Journal of Emerging Markets, 2011)
Domestic tourism in Australia generates about 74% of total tourism revenue. Given that, this paper examines whether changes in Australian households’ income and the prices of domestic travel can influence the demand for domestic travel. It reveals some notable results. First, Australian households will not choose to travel domestically when there is an increase in household income. Second, an increase in the current prices of domestic travel can cause the demand for domestic trips to fall in the next one or two quarters ahead. Finally, the coefficients for lagged dependent variables are negative, indicating perhaps, that trips are made on a periodic basis. Keywords: domestic tourism, Australia, households’ income, domestic travel